An overview of the mechanisms and potential roles of extracellular vesicles in septic shock - Cao, Meiling; Shi, Mingyue; Zhou, Boru; Jiang, Hongkun (Frontiers in Immunology, 2024)
Septic shock, a subset of sepsis, is a fatal condition associated with high morbidity and mortality. However, the pathophysiology of septic shock is not fully understood. Moreover, the diagnostic markers employed for identifying septic shock lack optimal sensitivity and specificity. Current treatment protocols for septic shock have not been effective in lowering the mortality rate of patients. Most cells exhibit the capability to release extracellular vesicles (EVs), nanoscale vesicles that play a vital role in intercellular communication. In recent years, researchers have investigated the potential role of EVs in the pathogenesis, diagnosis, and treatment of different diseases, such as oncological, neurological, and cardiovascular diseases, as well as diabetes and septic shock. In this article, we present an overview of the inhibitory and facilitative roles that EVs play in the process of septic shock, the potential role of EVs in the diagnosis of septic shock, and the potential therapeutic applications of both native and engineered EVs in the management of septic shock.